Cardiovascular Complications of SARS-CoV-2 Vaccines: An Overview - Shiravi, Amir Abbas; Ardekani, Ali; Sheikhbahaei, Erfan; Heshmat-Ghahdarijani, Kiyan (Cardiology and Therapy, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of the deadly disease known as coronavirus disease 2019 (COVID-19) that has reached pandemic proportions. Currently, there is no definitive treatment for COVID-19, although many vaccines have been developed. The World Health Organization has approved the safety and efficacy of the AstraZeneca/Oxford, Johnson and Johnson/Janssen (JnJ), Moderna, Pfizer/BioNTech, Sinopharm, and Sinovac vaccines so far. The approved formulations of AstraZeneca, JnJ, and Gam-COVID-vac (Sputnik V) contain DNA delivered within non-replicating recombinant adenovirus vector-based systems, while the Pfizer and Moderna vaccines utilize mRNA technology and lipid nanoparticle delivery systems. All of these vaccines encode production of the SARS-CoV-2 spike (S) protein, ultimately triggering immunity in the human body. COVID-19 causes several cardiovascular complications, such as arrhythmias, myocarditis, pericarditis, and venous thromboembolism. SARS-CoV-2 vaccines have been associated with rare, but sometimes fatal, cardiovascular side effects, which are the topics of this review. SARS-CoV-2 vaccines in general may cause thromboembolic events, such as cerebral vein thrombosis, and mRNA-based vaccines in particular may cause myocarditis/pericarditis, with the latter more likely to occur in younger adults after the second vaccination dose. Nevertheless, the advantages of these vaccines for ending the pandemic and/or decreasing the mortality rate outweigh any risk for the rare cardiovascular complications.